(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This articleи deals with the question of the spiritual experience of a person in philosophy, in addition, as indicated in it, the question of the essence of spiritual experience had various interpretations in philosophy. In the public mind, the very word spirituality is associated with religiosity or a religious understanding of the world. However, we must not blur the boundaries between spiritual and religious concepts. This article examines the relationship between the religious and spiritual experiences of people, as well as the criteria for assessing the degree of spiritual maturity of a person.